1986
DOI: 10.1029/ja091ia10p11123
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous polar cap and magnetotail observations of intense polar rain

Abstract: Six prolonged episodes of intense polar rain with average or above average temperatures occured during the four‐month period from mid‐February to mid‐June 1978. Electrons with energies up to 1 keV are observed throughout these events, and 9‐keV electrons occasionally are detected. To investigate whether this intense polar rain is accelerated within the magnetosphere, we compare DMSP F2 electron measurements made at low altitudes over the polar cap with near‐simultaneous ISEE 1 electron measurements made in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The electron fluxes exhibited field-aligned bi-directionality and were successfully identified to be the polar rain electrons, originating in the SW, with the most anisotropic part of them being the SW heat flux 'strahl' electrons. Greenspan et al (1986) compared electron spectra measured on ISEE 1 with polar rain measured on DMSP F2 and confirmed the conclusion that the electrons of both the intense and normal polar rain originate in the interplanetary medium. Based on ion spectra measurements aboard PROGNOZ 8 Vaisberg et al (1996) reported about tailward flowing cold oxygen beams, which were interpreted as being energised by impulsive convection (Delcourt et al, 1996).…”
Section: Introductionsupporting
confidence: 75%
“…The electron fluxes exhibited field-aligned bi-directionality and were successfully identified to be the polar rain electrons, originating in the SW, with the most anisotropic part of them being the SW heat flux 'strahl' electrons. Greenspan et al (1986) compared electron spectra measured on ISEE 1 with polar rain measured on DMSP F2 and confirmed the conclusion that the electrons of both the intense and normal polar rain originate in the interplanetary medium. Based on ion spectra measurements aboard PROGNOZ 8 Vaisberg et al (1996) reported about tailward flowing cold oxygen beams, which were interpreted as being energised by impulsive convection (Delcourt et al, 1996).…”
Section: Introductionsupporting
confidence: 75%
“…Satellite‐based imagers can monitor auroral emissions in the polar cap, but the observation of the aurora caused by the polar rain electrons is difficult due to the weak energy flux (0.001 to 0.01 ergs/cm 2 /s) of polar rain electrons [ Winningham and Heikkila , 1974]. Occasionally, intense keV polar rain electrons with energy flux up to a few ergs/s/cm 2 have been observed [ Foster and Burrows , 1976; Greenspan et al , 1986; Newell and Meng , 1990]. These keV polar rain electrons are intense enough to produce observable auroral emissions [ Zhang et al , 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, intense keV polar rain with energy flux of a few ergs/cm 2 /s and mean energy ≥ 1 keV were observed in the polar cap [ Foster and Burrows , 1976; Greenspan et al , 1986; Newell and Meng , 1990]. Based on a large DMSP particle database, Newell and Meng [1990] found that the intense keV polar rain events are the same phenomenon as ordinary polar rain and they can be observed over the course of hours.…”
Section: Introductionmentioning
confidence: 99%